2003
DOI: 10.1128/aem.69.1.679-682.2003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Natural Erwinia pyrifoliae Strains Deficient in Hypersensitive Response

Abstract: From necrotic tissue of a Nashi pear tree, 24 Erwinia pyrifoliae strains, found to be identical by pulsed-field gel electrophoresis analysis, were isolated. Thirteen strains were not virulent on immature pears and did not induce a hypersensitive response in tobacco leaves. The defective gene hrpL was complemented with intact genes from E. pyrifoliae and Erwinia amylovora.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…In fact, natural deletion of a type III secretion gene cluster in Salmonella spp. (14) and a natural HR-deficient Erwinia pyrifoliae strain have been reported (20). However, the inability of the E. pyrifoliae strain to cause HR was not due to the absence of the hrp genes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, natural deletion of a type III secretion gene cluster in Salmonella spp. (14) and a natural HR-deficient Erwinia pyrifoliae strain have been reported (20). However, the inability of the E. pyrifoliae strain to cause HR was not due to the absence of the hrp genes.…”
Section: Resultsmentioning
confidence: 99%
“…Rather, a single-base mutation of the regulatory gene, hrpL, was responsible for the absence of HR. In E. pyrifoliae, no difference in growth rate was observed in the HR-negative strain when it was coinoculated with an HRpositive strain at different ratios, suggesting that the HR-positive strain aids the growth of the HR-negative variant in host plant tissue (20). WPP17 was isolated from the same tuber as WPP16 and WPP18, two virulent strains able to elicit the HR, suggesting that growth of WPP17 could have been aided by these more virulent strains.…”
Section: Resultsmentioning
confidence: 99%
“…Strains lacking a functional T3SS have been reported for the plant pathogens Pseudomonas syringae (22) and Erwinia pyrifoliae (18). P. wasabiae differs from these plant pathogens since it lacks a T3SS, but it is still virulent.…”
Section: Discussionmentioning
confidence: 99%
“…that causes bacterial shoot blight of pear was reported to be more closely related to E. pyrifoliae than to the typical E. amylovora (Beer et al 1996;Jock et al 2003aJock et al , 2003bKim et al 2001a;McGhee et al 2002). In addition, a recent comparative study using amplified fragment length polymorphism (AFLP) and groEL sequence analysis showed that Erwinia pathogen of pear in Japan is closely related to E. pyrifoliae and is distinct from E. amylovora (Maxson-Stein et al 2003;Mizuno et al 2000).…”
Section: Introductionmentioning
confidence: 94%